Flow and heat transfer over a stretching cylinder with prescribed surface heat flux - Bachok @ Lati, Norfifah; Mohd Ishak, Anuar (Universiti Putra Malaysia Press, 2010)
The steady laminar flow caused by a stretching cylinder immersed in an incompressible viscous fluid with prescribed surface heat flux is investigated. The governing partial differential boundary layer equations in cylindrical form are first transformed into ordinary differential equations before being solved numerically by a finite-difference method. The problem under consideration reduces to the flat platecase when the curvature parameter is absent, and thus the results obtained can be compared with that case which is available in the literature as well as the exact solution, and found to be in good agreement. The solutions for the heat transfer characteristics are evaluated numerically for different parameters, such as the curvature parameter γ, and the Prandtl number Pr. It is observed that the surface shear stress and the heat transfer rate at the surface increase as the curvature parameter increases.